Context-specific functional effects of IFNGR1 promoter polymorphism. - Koch, O; Kwiatkowski, D; Udalova, I (2006)
We report evidence of a polymorphism in the promoter region of IFNGR1 (encoding interferon-gamma receptor 1) that has opposite functional effects in different cellular contexts. It is a deletion/insertion polymorphism that is found in Africans but not Europeans or Asians, and has been associated with resistance to severe malaria. We find that the IFNGR1-470del allele acts to suppress binding of nuclear proteins to the IFNGR1 promoter region in a manner that is specific for cell type. In B-lymphocytes, the IFNGR1-470del allele suppresses the binding of a approximately 35 kDa nuclear protein and acts to increase reporter gene expression. In epithelial cells, the same allele acts to decrease gene expression and suppresses the binding of approximately 90 kDa STAT-1 and STAT-2 proteins. In T-lymphocytes, this allele causes only subtle differences in nuclear protein binding and has no significant effect on gene expression. These findings suggest a mechanism by which a single genetic variant may cause a broad range of phenotypic consequences.